E-Library Use and Employee Competence Effects on Service Quality at Muhammadiyah Makassar Library - Siti Marhumi; Nurinaya Nurinaya; Jamhaerani Jamhaerani; Nur Qalbi Albar; Nur Asastri Jani (Penerbit Goodwood, 2025)
Purpose: This study examines the extent to which e-library services and employee competence influence service quality at the Library of the University of Muhammadiyah Makassar. Research Methodology: The research was conducted at the University of Muhammadiyah Makassar Library using a descriptive quantitative design. The population comprised 6,576 visitors who accessed the e-library, and a purposive (non-probability) sampling technique was applied to select 99 respondents. Results/findings: The results show that the e-library variable has a positive and statistically significant effect on service quality (p < 0.05). Employee competence also has a positive and statistically significant effect on service quality (p < 0.05). Conclusions: Improving e-library services and strengthening employee competence are both important drivers of higher perceived service quality in the university library context. Limitations: The study is limited by the use of purposive sampling and data collected from a single university library, which may restrict generalizability to other institutions. Contribution: This study contributes empirical evidence to library and information science by clarifying how digital library services and staff competence jointly shape service quality. The findings can support library managers and university administrators in prioritizing technology-related service improvements and competency development programs.